Clinical characteristics of patients with atrial flutter before radiofrequency ablation - Pavlova, Daiana; Brynza, Mariia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Introduction. Radiofrequency ablation (RFA) is today the method of choice for the ineffective medical treatment of atrial fibrillation (AF), but its course is often complicated by comorbid pathology. The predicted great impact of these nosologies on the effectiveness of radiofrequency ablation of the arrhythmia substrate requires additional study before RFA.Objectives – to analyze the clinical characteristics of patients with isolated atrial fibrillation and combination with of atrial fibrillation with atrial flutter (AF + AFib) that underwent radiofrequency ablation of the arrhythmia substrate.Materials and methods. 84 patients aged 65 ± 9 (82.3 % of men) were examined, who underwent RFA of the arrhythmia substrate: cavo-tricuspid isthmus (CTI) or combined with pulmonary veins isolation (CTI + PV) strategy for patients with AFib. Before radiofrequency ablation, the following clinical indicators were assessed: forms of AF + AFib, the presence of chronic heart failure (CHF) and functional classes (FC) according to NYHA classification, the forms of chronic coronary syndromes (CCS): postinfarction cardiosclerosis, syndrome-X, functional classes of stable angina (SA), stages of arterial hypertension (AH), the presence of type 2 diabetes or stroke in the anamnesis.Results. Radiofrequency ablation of isolated atrial fibrillation was more often performed for persistent arrhythmia in patients with stable angina III FC, arterial hypertension stage 2 and 3, radiofrequency ablation of combination of atrial fibrillation with atrial flutter – equally often for persistent or paroxysmal form in patients with SA I and II class, AH stage 2 and 3; in both cases patients with chronic heart failure II and III FC more often needed radiofrequency ablation of the arrhythmia substrate.Conclusions. Given the lack of correlation between clinical and demographic characteristics, it is advisable to continue studying their prognostic effect on the course of comorbid pathology and treatment of patients after radiofrequency ablation of the arrhythmia substrate of atrial fibrillation and combination of atrial fibrillation with atrial flutter.